2005
DOI: 10.1007/s10397-005-0112-x
|View full text |Cite
|
Sign up to set email alerts
|

Painless vaginal hysterectomy with thermal hemostasis (results of a series of 152 cases)

Abstract: In a preceding paper the authors described a completely new approach for vaginal hysterectomy. The classical technique has been simplified, including thermal hemostasis with BiClamp, multimodal anesthesia, and ongoing research aimed at ensuring minimal trauma. The authors describe the first group of 152 patients who were treated with this new approach. The results show that it is possible to expand the range of vaginal indications while shortening the patient's hospital stay to 1 day. Furthermore, this innovat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 10 publications
4
18
0
Order By: Relevance
“…However, since Clavé used long-acting regional and local anesthesia, this represents a considerable limitation on the validity of the conclusions with regard to the effects of bipolar coagulation, so that no clear difference could be made between the effects on the postoperative course. In a more recent study in 152 patients, he confirmed his earlier conclusions [5]. We were also able to show in a retrospective study with 40 patients in each group that patients who underwent surgery using the BiClamp had less blood loss during surgery, less postoperative pain, and were also able to be discharged earlier (Table 1); in the 19 patients who underwent only vaginal hysterectomy, the blood loss and postoperative pain were significantly lower [6,7].…”
Section: Results Of Studiessupporting
confidence: 83%
“…However, since Clavé used long-acting regional and local anesthesia, this represents a considerable limitation on the validity of the conclusions with regard to the effects of bipolar coagulation, so that no clear difference could be made between the effects on the postoperative course. In a more recent study in 152 patients, he confirmed his earlier conclusions [5]. We were also able to show in a retrospective study with 40 patients in each group that patients who underwent surgery using the BiClamp had less blood loss during surgery, less postoperative pain, and were also able to be discharged earlier (Table 1); in the 19 patients who underwent only vaginal hysterectomy, the blood loss and postoperative pain were significantly lower [6,7].…”
Section: Results Of Studiessupporting
confidence: 83%
“…A significant reduction in hospital stay was also seen by Clave et al (6 days v/s1 day), Ding et al (1.2 vs 3 days), Lewy et al (1 vs 3 days) and Zubke et al (6.6 vs 7.4 days). 16,18,20,23 Cronje and de Coning did not find a significant difference. 19 We conducted present study on a mixed group of patients with various indications, with different surgical difficulties in different groups.…”
Section: Discussionmentioning
confidence: 76%
“…Then, we have evaluated the resources estimating the cost of materials, the stay in hospital and the time of surgery, for each patient, and the quality of the treatment in terms of resumption of social or working life. Germany) is a bipolar forceps system that allows safe haemostasis of large vessel and it can use to grasp the tissue requiring separation [5][6][7][8][9][10][11][12][13]. Bipolar current flows between the branches of the forceps, while the Erbe Vio System automatically regulates the current waveforms and the voltage [9].…”
Section: Methodsmentioning
confidence: 99%
“…BiClamp Ò bipolar coagulation forceps has been available for open surgery procedures since 2002 [12]. Vaginal hysterectomy with BiClamp Ò represents an example of mininvasive surgery and could be a valid and cost-benefit alternative in the surgical treatment of benign gynaecologic disease [10,13]. The surgery may be performed by Kenlet's multimodal anaesthesia that consisted with an association of a general and local anaesthesia with paracervical and pudendal anaesthetic block, with a better control of a better control of pain and postoperative outcome [15,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation